STRATEGI PENINGKATAN KINERJA SUMBER DAYA MANUSIA PADA YAYASAN YAMARU SAYAP KASIH - Soares, Yohanes; Sayidah, Nur; Ady, Sri Utami (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of writing this research is to find out the results of a SWOT analysis of employee performance improvement strategies carried out by human resource management at the Yamaru Wing Kasih Foundation. and strategies to improve employee performance carried out by human resource management at the Manuel Runtu Tomohon Foundation. The data method used in this research is SWOT. SWOT shows that the position of the Manuel Runtu Foundation is in quadrant 1 (+,+). This means that the Foundation has opportunities and strengths that can be utilized for foundation development programs. Position in quadrant I, theoretically, means that the strategy that must be implemented by the Foundation is a strategy that supports aggressive growth policies (growth oriented strategy) or an aggressive strategy. The review of internal conditions including organization, governance, resources and performance of Yamaru Wing Kasish directs all foundation organs towards one virtue, namely professional management of the foundation. To be able to take advantage of opportunities and face challenges that occur in the external environment, professionalism is seen as an urgency. The initial step is to organize a planning system based on strategic planning.